مستويات استراتيجية التعاون التنافسي و دورها في بناء القدرات الدينامية للمنظمات : دراسة استطلاعية تحليلية في الشركة العربية لصناعات المضادات الحيوية و مستلزماتها (اكاي) - د. معن وعدالله المعاضيدي; ايمان عبد محمد (PROSPECTIVE RESEARCHES, 2023)
The research aims to answer two questions. First to which level can the organizations cooperate with their competitors and complementaries, i.e. (Macro, Meso, and Micro)? Second, what is the role of the dynamic capabilities in the assurance of keeping and continuing competitive organization success under the competitive coopetition strategy? Hence, the Arabic Company for Antibiotics Industries and its Appliances (A.C.A.I) is selected as a field of study which is based on questionnaire. The Sample of the study includes the managers of all departments and units in the researched company, they are (56) managers. The researchers used some of statistical tools in data analysis such as: Pearson and Spearman-Brown correlation coefficients, simple and stepwise regression. Field analysis affirms the performance of relations between variables under research that’s why it is possible to adopt the competitive coopetition strategy by organizations as a successful strategic choice, which opens gate between organizations to learn and ally with each others in developing capabilities and achieving higher benefits.